THE INFLUENCE OF COMPANY CULTURE ON STARTUP FINANCIAL PERFORMANCE - Indra Wijaya; Kaito Tanaka; Herdi Herdi (Journal of Social Entrepreneurship and Creative Technology, 2025)
The culture within a company is increasingly recognized as a critical factor influencing its overall performance, particularly in startups where innovation, adaptability, and employee engagement are crucial to success. While numerous studies have explored the relationship between company culture and organizational outcomes, limited research has focused specifically on the financial performance of startups. This research aims to examine the influence of company culture on the financial performance of startups, identifying key cultural elements that drive profitability, growth, and long-term sustainability. A mixed-methods approach was employed, combining quantitative data from financial performance metrics of 50 startups with qualitative insights gathered through interviews with founders and key employees. The findings suggest a strong correlation between positive company culture—characterized by open communication, employee empowerment, and a collaborative environment—and higher financial performance. Startups with a culture of innovation and continuous learning tend to achieve greater revenue growth and profitability, while those with hierarchical and rigid cultures face challenges in scaling. The study concludes that fostering a supportive, flexible, and innovative company culture is essential for startup success, particularly in fast-paced and competitive industries. This research contributes to a deeper understanding of the intangible factors that drive financial outcomes in startups, offering valuable insights for entrepreneurs seeking to enhance both organizational culture and financial performance.